Synchronous Duodenal and Pancreatic Metastases From Clear Cell Renal Cell Carcinoma 18 Years After Nephrectomy: A Case Report - Ankit Kulkarni; Suhail Sapkota; Sai Sushrutha Mudupula Vemula; Shreya Motkur; Adarsh Jha; Rutwik Pradeep Sharma; Sumugdha Rayamajhi (Clinical Case Reports, 2026)
ABSTRACT A 63‐year‐old man presented with melena and severe anemia 18 years after nephrectomy for clear cell renal cell carcinoma. Imaging and biopsy confirmed duodenal and pancreatic metastases mimicking pancreaticobiliary malignancy. He underwent pancreaticoduodenectomy. This case highlights delayed RCC recurrence and the role of complete resection despite significant perioperative morbidity.